Dampak AI Terhadap Metode Pembelajaran Bahasa Yang Adaptif Dan Personal - Shira Alegra, Ghaitsa (Universitas Siber Indonesia, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on more adaptive and personalized language learning methods. This research can aim to analyze the effectiveness of AI in enhancing the language learning experience, using a quantitative approach through a questionnaire survey of 116 respondents from various educational levels. The results of this study have shown that AI is able to customize learning materials based on individual abilities, provide instant feedback, and create an interactive and fun learning experience through features such as chatbots, voice recognition, and gamification. The majority of the respondents were from the 18-24 age group with a Bachelor's degree, indicating that the younger generation is utilizing this technology more. AI can be proven to increase students' learning motivation, effectiveness, and confidence in learning various foreign languages. As such, AI offers a more personalized and flexible approach to learning compared to traditional methods, while opening up new opportunities in the technology-based education sector.